I'idami inqilabi-yi Abbas Shahriari, mardi hizar chihrah buzurgtarin jasus va mushaviri 'ali-yi sazmani amnyyati Iran bah vasilahi-yi Sazmani Chirikhai-yi Fada'i-yi Khalqi : (Sazmani Chirikhai-yi Fada'i-yi Khalqi Iran)
The revolutionary execution of Abbas Shahriari, the one thousand faced man, the master spy and the chief advisor to Iranian security organisation by Organization of Iranian People's Fadai Guerrillas and a response to the message issued by the remnants of the Tudah Party leadership.